APLIKASI RAJUTAN BAMBU SEBAGAI TULANGAN BALOK BETON - Pinto, Agostinho Francisco; Dewi, Sri Murni; Nurlinah, Devi (Media Teknik Sipil, 2016)
Need for the use of reinforced concrete in housing construction will increase along with the rapid population growth. This increases the need for steel reinforcement as a major component. The increase in need for steel reinforcement will trigger a price increase so that it becomes expensive and scarce. Iron ore as a raw material for making steel reinforcement is a mineral that can not be renewed. Therefore, efforts to use alternatives to steel reinforcement in concrete. Bamboo has good mechanical properties and a high ratio between strength and weight. Bamboo has a tensile strength is high, between 100-400 MPa, nearly matching the tensile strength equivalent to steel reinforcement ½ to ¼ of iron ultimate voltage (Widjaja, 2001) and (Surjokusumo and Nugroho, 1993) showed similar results and by the Moriscos, 1996 that the tensile strength of bamboo can reach 1280 kg / cm2. Bamboo can be used as the material of reinforced concrete. This study aims to determine the capacity of the bending beam with reinforcement of bamboo, bamboo reinforced beam deflection capacity. This experiment is a concrete beam bending test. The results showed that bamboo reinforced concrete beam has a maximum capacity reached 56.61% of the maximum capacity of steel reinforced concrete.